USING MODERN TECHNOLOGIES IN TEACHING MOTHER TONGUE AND LITERATURE LESSONS (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: In the modern educational landscape, the integration of technology into teaching methods has become essential, particularly in language and literature education. This paper explores the effective use of modern technologies such as interactive whiteboards, multimedia presentations, educational platforms, and digital storytelling tools in teaching mother tongue and literature lessons. The use of such technologies not only enhances student engagement but also improves comprehension and creativity. The study highlights practical methods for incorporating these tools into lessons and examines their impact on learners' academic performance and motivation. By blending traditional teaching approaches with digital tools, educators can create a more dynamic and student-centered learning environment.